Global Rangelands Data Platform MVP - GMV Innovating Solutions; International Livestock Research Institute (International Livestock Research Institute, 2022)
This project aims at contributing to the UN resolution 2/24 on combating desertification, land degradation and drought and promoting sustainable pastoralism and rangelands; and UN resolution 4/15 on innovations in sustainable rangelands and pastoralism, as well as the UNEP-led gap analysis on rangelands and the resulting report: Rangelands: A case of benign neglect. This rangeland resource assessment was also to complement the global Rangelands Atlas produced in 2021 as a collaboration between UNEP, ILRI and other stakeholders; contribute to a baseline for the development of a GEF-funded global project on rangeland restoration and the development of a rangeland monitoring system for Africa led by the European Space Agency. The assessment contributes to discussions and interventions focusing on One Health, with rangelands health being an important pillar of this, as well as sustainable food systems. This includes attention to such as land degradation, climate impacts on livestock and other environmental challenges, and allows better analysing opportunities for more sustainable investments in rangelands through restoration or other livestock production systems. As part of this assessment, this document defines the objectives for the development of a Minimum Viable Product (MVP) for a Global Rangelands Data Platform.